Synthetic copolymer (AM/AMPS/DMDAAC/SSS) as rheology modifier and fluid loss additive at HTHP for water‐based drilling fluids. Issue 30 (7th April 2019) - Huang, Yuming; Zhang, Dingyu; Zheng, Wenlong
ABSTRACT: In the petroleum industry, high temperature and high pressure (HTHP) would dramatically worsen rheological properties and increase fluid loss volumes of drilling fluids. Synthetic polymer as an indispensable additive has attracted more and more attention recently. In this article, a new copolymer (named AADS) of 2‐acrylamide‐2‐methylpropanesulfonic acid, acrylamide, dimethyl diallyl ammonium chloride, and sodium styrene sulfonate was synthesized through aqueous solution polymerization. The chemical structure of the copolymer was characterized by Fourier transform infrared spectroscopy and nuclear magnetic resonance. Moreover, its thermal stability was simultaneously analyzed using a differential scanning calorimetry. The results showed that the synthetic polymer contained all the designed functional groups, and its structure was consistent to the desired one. Under contamination of sodium chloride, AADS solution maintained relatively high viscosity in high concentration brine, showing a good antisalt capacity. Furthermore, the effect of AADS content and temperature on rheological behavior and fluid loss volume of the water‐based drilling fluid (WBDF) containing the synthesized product were investigated according to the American Petroleum Institute standard. Results showed that the rheological and filtration properties of the prepared WBDF were improved with the increase in the AADS concentration before and after the thermal aging test. In addition, in the temperature range of 80–240 °C, a reversible rheological behavior was observed during the heating–cooling process, and the HTHP fluid loss was controlled within 22.5 mL, suggesting that the copolymer AADS was suitable for making WBDF s with high temperature resistance. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47813. Abstract : AADS is a synthetic copolymer that can adsorb and ensphere on the surface of clay particles, and thus protecting the clay particles from dispersing or aggregating when subjected to high temperature.